HUBUNGAN ANTARA POWER OTOT TUNGKAI DAN DAYA TAHAN TERHADAP HASIL DAYUNG ROWING DALAM OLAHRAGA DAYUNG DI SMA NEGERI OLAHRAGA PROVINSI RIAU - Pratama, Nanda Eka; Zainur, Zainur; Sulastio, Agus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstrak: The aim of this study is to determine whether there is a connection between limb muscle strength and endurance with rowing. This results in rowing at the Riau State Sports High School. The sample of this study is 10 athletes at Paddle State High School in Riau province. The sampling technique was taken in total (total sampling) or a full sampling technique on the Athlete Paddle Athletes of Riau State Sports High School for a total of 10 people. The results of the correlation with athletes are rowing high school sports in the Riau province where the first analysis between leg muscle X1 and Y where rtab is at a significant level É‘ (0.05) = r_calculate (0.214) <r_tab (0.666), meaning the hypothesis becomes accepted and there is a small relationship between leg muscle power and rowing results at the High School Athletes Rowing in Riau province. From the calculation of the second analysis of X2 and Y, where r_tab is at a significant level É‘ (0.05) = r_count (0.119) <r_tab (0.666), meaning the hypothesis is accepted and there is a relationship between endurance and rowing results in Paddle Athletes High School in the province of Riau. The third analysis of the relationship between leg muscle strength (X1) endurance (X2) and the results of rowing (Y) where rtab at a significant level É‘ (0.05) = r_calculate (0.702) <r_tab (0.666), it can be concluded that the relationship between (X1) and (X2) with (Y) or the relationship between leg muscle strength and resistance to rowing Rowing Results in rowing sports in Riau State High School Sports in moderate intervention.Key Words: Power Legs, Endurance, Ergometer